Upaya Penanganan Krisis Relasi Media DPR dalam Kontroversi UU MD3 - Indah Fajar Rosalina (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2020)
Law No. 17 of 2014 concerning MD3 (MPR / DPR / DPRD) has been legally promulgated to become Law No. 2 of 2018 in February 2018. The birth of an article in the revision of the MD3 Law reaped this controversy among the public and the media. Many media that consider changes to Article 121 k, Article 245, and Article 73 will strengthen the power of the House of Representatives as an institution that is anti-criticism, cannot be convicted without permission of the MKD (Council Honorary Council), and easily criminal anything that suits your needs. In carrying out its mandate as a people's representative, the House of Representatives approved the media for media coverage. This report increased public opinion about the DPR's performance. For this reason, communication management is needed to build public trust in DPR institutions through media relations. Community trust and dignity, as well as the integrity of the institution and its members are very important, so that security products such as MD3 Law will have strong legitimacy and be accepted by the community. Departing from these problems, this study discusses the workings of the media relations in the House of Representatives in reducing the crisis that hit his institution. This research is a qualitative study using research strategies that discuss evolution with media relations. The research source was obtained from the processing of some related data, and also in-depth interviews of the Chair and Staff of the Indonesian Parliament News Office, and the Chair of the Parliamentary Journalists' Organization. The researcher tries to analyze how to overcome the recovery of the DPR in this issue. Planning, repairs, crises, the DPR is not optimal, because repairs, crises, the creation of a one-door system for distributing information, and the weak trust of the media and the public for the integration of the DPR itself.